Impact of surgical timing on early functional and cognitive recovery after aneurysmal subarachnoid hemorrhage: the role of early rehabilitation - Pešterac-Kujundžić, Angelka; Ilić, Nela; Bogosavljević, Vojislav; Milovanović, Andjela; Tomanović Vujadinović, Sanja; Nedeljković, Una (Vojnosanitetski pregled, 2025)
Background/Aim. Aneurysmal subarachnoid hemorrhage (aSAH) is a critical condition with significant functional and cognitive consequences. The optimal timing for surgical intervention remains controversial, particularly regarding early recovery. The aim of this study was to evaluate early functional and cognitive recovery in patients treated with early vs. delayed surgery, all of whom participated in a standardized early rehabilitation program. Methods. This prospective single-center cohort study included 114 patients who underwent surgery for ruptured intracranial aneurysms between November 2022 and November 2023. Patients were divided into two groups: the early surgery group, where the surgery was performed within three days after aneurysm rupture, and the delayed surgery group, where the surgery was performed more than three days after rupture. Functional status was assessed using the Functional Independence Measure (FIM) scale, and cognitive status was assessed using the Mini-Mental State Examination (MMSE). Both tests were administered at the start and end of the early rehabilitation program. Descriptive and inferential statistical methods (Wilcoxon signed-rank test, split-plot analysis of variance) were used for data analysis. Results. A statistically significant improvement in both functional and cognitive scores was achieved in both groups during the early rehabilitation program (p < 0.001). The greatest improvement was achieved in the FIM motor subscale. At discharge, the early surgery group achieved significantly higher FIM motor and total scores compared to the delayed surgery group (p = 0.024, p = 0.037, respectively). No statistically significant differences were found between the groups in MMSE or FIM cognitive scores. The severity of hemorrhage significantly affected changes in MMSE and FIM scores. Age, length of hospital stay, and the time period until rehabilitation initiation did not significantly influence patient recovery. Conclusion. Early surgical intervention for aSAH, combined with a standardized rehabilitation program, is associated with better early motor functional recovery compared to delayed surgery. Individualized rehabilitation strategies may be needed for patients who underwent delayed surgery.